Experimental animation and the neosurrealist remediation of popular music video. Issue 1 (1st December 2020) - Perrott, Lisa
Once appearing to function primarily as a commercial tool for popular entertainment, the popular form of music video has recently been exposed by scholars as formally and functionally diverse, with a rich history stretching back decades before the advent of MTV. Animated music videos owe much to centuries old traditions spanning the visual, musical and performing arts, providing performative and material models that inspire contemporary video directors. Experimental animation, surrealism and music video form a matrix of historical and contemporary significance; however, few scholars have undertaken close examinations of the relations between them. John Richardson and Mathias Korsgaard show how music video directors have employed surrealist compositional strategies together with experimental animation methods, thus giving rise to challenging new forms that traverse disparate approaches to art and culture. Building upon their contributions, this article explores the continuity between experimental animation, surrealism and music video, with a view to discovering the subversive potential of this matrix. In order to probe this potential, the author examines how music video directors experiment with animation technique as a means of subversion and enrichment of popular music video. Through close analysis of music videos directed by Adam Jones, Stephen Johnson, Floria Sigismondi and Chris Hopewell, this article charts the continuity of surrealist strategy across culturally specific moments in history, thus provoking questions around the perceived functions of animated media and popular music video.